Exploring Students’ Experiences at the Eastern Cape Voice Symposium - Nyiko Condry Ngobeni; Njabulo Sifiso Mthinmkhulu (Universitas Negeri Semarang, 2025)
The Eastern Cape Voice Symposium brought together 21 voice students from Nelson Mandela University, Rhodes University, and the University of Fort Hare, alongside lecturers from these institutions and Walter Sisulu University, as well as three prominent African composers. This study investigates the educational and artistic impact of the symposium on students’ development, and how collaboration among lecturers and composers shaped students’ understanding of African vocal music. Employing a qualitative case study design, data were collected through semi-structured interviews with nine students who voluntarily participated in the research. While 21 students attended the symposium, only nine responded to the interview questions and reflected on their experiences. Thematic analysis was used to explore themes of academic growth, performance development, and cultural engagement. Findings indicate that the symposium enhanced students’ vocal technique, artistic confidence, and appreciation for African compositions. Students also valued exposure to diverse pedagogical approaches, cross-institutional collaboration, and the mentorship of African composers. The event fostered critical reflection on African identity and practice in voice training. This study recommends institutionalising similar symposia as platforms for collaborative learning, cultural exchange, and curriculum transformation. It contributes to current scholarship by demonstrating the potential of short-term, immersive educational events to support decolonised, culturally responsive music education in South Africa.